Diced and grounded broadband bow‐tie antenna with tuning stub for resonant tunnelling diode terahertz oscillators. Issue 3 (6th December 2016) - Alharbi, Khalid Hamed; Khalid, Ata; Ofiare, Afesomeh; Wang, Jue; Wasige, Edward
Abstract : Radiation from antennas integrated with indium phosphide (InP)‐based resonant tunnelling diode (RTD) oscillators is mainly through the substrate because of the effects of the large dielectric constant. Therefore, hemispherical lenses are used to extract the signal from the backside of the substrate. In this study the authors present a broadband bow‐tie slot antenna with a tuning stub which is diced and mounted on a ground plane to alleviate the substrate effects. Here, the large dielectric constant substrate around the antenna conductor is removed. In addition, the ground plane underneath the diced substrate acts as a reflector and, ultimately, the antenna radiates to the air‐side direction. Antenna integration with RTD oscillators is described in this study as well. Two‐port bow‐tie slot antennas were designed and characterised and showed the suitability of integration with power combining RTD oscillator circuits which are based on mutual coupling. The antennas were fabricated using electron beam lithography on a semi‐insulating InP substrate. Simulated and measured bandwidth almost extends the entire frequency range 230–325GHz. Simulations shows air‐side radiation pattern and antenna gain of around 11dB at 280GHz. Simulations also show that the antenna may be fed with a 50‐Ω or 30‐Ω feed line, i.e. suitable feed lines, without compromising its performance which may prove beneficial for optimum loading of RTD oscillators.